The Effect of Transformational Leadership Style and The Work Environment on Employee Performance at Angkasa Notebook Trading Enterprise in Bandar Lampung - Felix Jasarta; M. Oktavianur (Cita konsultindo, 2026)
This study examines the effect of transformational leadership style and the work environment on employee performance at Angkasa Notebook Trading Enterprise in Bandar Lampung City. A quantitative survey approach was employed, involving all 33 employees as the research sample through a saturated sampling technique. Data were collected using Likert-scale questionnaires and analyzed using multiple linear regression with SPSS. The findings reveal that transformational leadership style and the work environment each have a positive and significant effect on employee performance. Simultaneously, both variables significantly influence employee performance, with a coefficient of determination of 52.3%. These results highlight the importance of effective transformational leadership and a conducive work environment in enhancing employee performance in small and medium-sized trading enterprises.